THE CORRELATION BETWEEN NURSES' CAREER PATHS TO THE JOB SATISFACTION OF IMPLEMENTER NURSES IN THE WARD OF WANGAYA HOSPITAL - Pradiptha, I Dewa Agung Gde Fanji; Sriadi, Nyoman Putri; Dewi, I Dewa Ayu Marokta Utami; Kartini Putri, Ni Putu Maya (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
The greater the number of employees who work at a company will increase the problem possibility, the handling of these problems depends on management's awareness of the importance of human resources in an organization. Human resources are the main resources in a company need a career planning and development. A good nurse career path enables to influence the improvement of work nurses satisfaction. This study aimed at analyzing the correlation between nurses' career paths to the job satisfaction of implementer nurses in the Ward of Wangaya Hospital. This research used correlation design research with cross sectional approach. The total sampling of the research were 125 implementer nurses. The data analysis technique used was univariate analysis to explain or describe the characteristics of the research variables and the bivariate analysis used in this study is the chi square test to analyze the correlation between nurses' career paths to the job satisfaction of implementer nurses in the Ward of Wangaya Hospital. The statistical test results obtained p value = 0.001, this indicates that there was a correlation between career paths and job satisfaction of implementer nurses in the Ward of Wangaya Hospital. It is important for hospital to provide opportunities for implementer nurses to improve their career paths, one of which is through further education, so that nurse job satisfaction can increase.